Dynamics of selected biological indices of Labeo rohita (Hamilton, 1822) in East Kolkata wetlands, a Ramsar site - Kumar, Avinash; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2022)
Selected biological indices of Labeo rohita such as length-weight relationships (LWR), relative condition factor (Kn), relative length of gut (RLG), gastro-somatic index (GaSI), hepato-somatic index (HSI), and gonado-somatic index (GSI) were studied in the East Kolkata wetlands. A total of 358 samples (176 male and 182 female) of L. rohita were collected at fortnightly intervals for one year using dragnet. The exponent ’b’ value of the length-weight relationship was 3.073, 3.026, and 3.048 for males, females and the pooled sample, respectively showing isometric growth of the fish. The Kn value varied from 0.95 to 1.07 exhibiting a significant difference (p<0.05) between sex. Mean RLG values fluctuated from 5.10 to 8.51 with significant differences (p<0.05) in different months. The average GaSI values ranged from 0.57 to 1.36 and mean HSI values from 0.53 to 1.41. The GSI values fluctuated from 0.95 to3.31and varied significantly (p<0.05) between the sex. Key words Labeo rohita; bio-indices; East Kolkata Wetlands; Ramsar site